Catechol-O-methyl transferase suppresses cell invasion and interplays with MET signaling in estrogen dependent breast cancer - Janacova, Lucia; Stenckova, Michaela; Lapcik, Petr; Hrachovinova, Sarka; Bouchalova, Pavla; Potesil, David; Hrstka, Roman; Müller, Petr; Bouchal, Pavel (Scientific reports, 2023)
Catechol-O-methyl transferase (COMT) is involved in detoxification of catechol estrogens, playing cancer-protective role in cells producing or utilizing estrogen. Moreover, COMT suppressed migration potential of breast cancer (BC) cells. To delineate COMT role in metastasis of estrogen receptor (ER) dependent BC, we investigated the effect of COMT overexpression on invasion, transcriptome, proteome and interactome of MCF7 cells, a luminal A BC model, stably transduced with lentiviral vector carrying COMT gene (MCF7-COMT). 2D and 3D assays revealed that COMT overexpression associates with decreased cell invasion (p < 0.0001 for Transwell assay, p < 0.05 for spheroid formation). RNA-Seq and LC-DIA-MS/MS proteomics identified genes associated with invasion (FTO, PIR, TACSTD2, ANXA3, KRT80, S100P, PREX1, CLEC3A, LCP1) being downregulated in MCF7-COMT cells, while genes associated with less aggressive phenotype (RBPMS, ROBO2, SELENBP, EPB41L2) were upregulated both at transcript (|log2FC|> 1, adj. p < 0.05) and protein (|log2FC|> 0.58, q < 0.05) levels. Importantly, proteins driving MET signaling were less abundant in COMT overexpressing cells, and pull-down confirmed interaction between COMT and Kunitz-type protease inhibitor 2 (SPINT2), a negative regulator of MET (log2FC = 5.10, q = 1.04-7). In conclusion, COMT may act as tumor suppressor in ER dependent BC not only by detoxification of catechol estrogens but also by suppressing cell invasion and interplay with MET pathway.
Keywords: estrogeny; Neoplasms; receptory pro estrogeny; katecholestrogeny; Catechols; tandemová hmotnostní spektrometrie; katecholy; katechol-O-methyltransferasa; Estrogens, Catechol; nádory; Tandem Mass Spectrometry; Catechol O-Methyltransferase; Estrogens; Receptors, Estrogen